Aptamer-facilitated Protection of Oncolytic Virus from Neutralizing Antibodies - Darija Muharemagic; Anna Zamay; Shahrokh M Ghobadloo; Laura Evgin; Anna Savitskaya; John C Bell; Maxim V Berezovski (Elsevier, 2014)
Oncolytic viruses promise to significantly improve current cancer treatments through their tumor-selective replication and multimodal attack against cancer cells. However, one of the biggest setbacks for oncolytic virus therapy is the intravenous delivery of the virus, as it can be cleared from the bloodstream by neutralizing antibodies before it reaches the tumor cells. We have selected DNA aptamers against an oncolytic virus, vesicular stomatitis virus, using a competitive binding approach, as well as against the antigen binding fragment (Fab) of antivesicular stomatitis virus polyclonal antibodies, in order to shield the virus from nAbs and enhance its in vivo survival. We used flow cytometry to identify these aptamers and evaluated their efficiency to shield vesicular stomatitis virus in a cell-based plaque forming assay. These oligonucleotides were then modified to obtain multivalent binders, which led to a decrease of viral aggregation, an increase in its infectivity and an increase in its stability in serum. The aptamers were also incubated in nondiluted serum, showing their effectiveness under conditions mimicking those in vivo. With this approach, we were able to increase viral infectivity by more than 70% in the presence of neutralizing antibodies. Thus, this method has the potential to enhance the delivery of vesicular stomatitis virus through the bloodstream without compromising the patient's immune system.